Penerapan Algoritma K-Nearest Neighbor dalam Klasifikasi Penyakit Gagal Jantung - Setiawati, Ni Ketut Intan; Wibawa, I Gede Arta (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2022)
Heart failure is a clinical syndrome caused by an abnormality in the structure of the heart's function that causes the heart to be unable to pump adequate amounts of blood so that the body does not receive enough nutrients for metabolic needs. The high prevalence of heart failure needs serious attention so that it can be treated early and reduce the risk of complications. Along with the development of technology, various classification methods have been used by other researchers to determine whether a person has heart failure or not. In this study, the classification of heart failure will use the K-Nearest Neighbor algorithm. K-Nearest Neighbor (KNN) is a classification algorithm based on the proximity of data to other data. The results of this study are the best accuracy values obtained with k = 7, where after going through an evaluation with the confusion matrix, the accuracy of the classification of heart failure with KNN is 91%.